2021
DOI: 10.1007/s11605-021-04988-1
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Application and Outcome of Non-operative Management of Acute Appendicitis in the Setting of COVID-19: Systematic Review and Meta-analysis

Abstract: Background Non-operative management (NOM) of acute appendicitis has been assessed in several studies before COVID-19 pandemic. This systematic review aimed to assess the extent of adoption, efficacy, and safety of NOM of acute appendicitis in the setting of COVID-19. Methods This was a PRISMA-compliant systematic review of the literature. Electronic databases and Google Scholar were queried for studies that applied NOM of acute appendicitis during COVID-19. The main out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 37 publications
2
56
0
3
Order By: Relevance
“…About the management of AA, 81% of our patients underwent surgery as the preferred modality of treatment; this differs from the practice reported in some hospitals that suggest conservative management of patients with the diagnosis of SARS-CoV-2 and acute abdomen. 6 , 7 Some centers have used more conservative approaches for uncomplicated cases of AA in patients with COVID-19, including home care and nonoperative management with antibiotics. 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About the management of AA, 81% of our patients underwent surgery as the preferred modality of treatment; this differs from the practice reported in some hospitals that suggest conservative management of patients with the diagnosis of SARS-CoV-2 and acute abdomen. 6 , 7 Some centers have used more conservative approaches for uncomplicated cases of AA in patients with COVID-19, including home care and nonoperative management with antibiotics. 23 …”
Section: Discussionmentioning
confidence: 99%
“… 5 In the context of COVID-19, nonoperative management of AA is an alternative to surgery with low failure and complication rates. 6 …”
mentioning
confidence: 99%
“…The management of acute appendicitis involves, if possible, conservative treatment as an outpatient, short hospitalization, operation with an open technique and under regional anesthesia [16]. AA was managed conservatively in 5.4-22.2% of the patients during the prepandemic period, which increased to 7.8-100% during the pandemic [30]. In our study, conservative treatment was performed in 46.8% (36/77) of the AA patients with 5.5% (n=2) recurrence rate during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the usage of NOT and the resulting outcomes of AUA in the setting of COVID-19 was systematically reviewed. The results indicated that NOT was a safe, short-term alternative to surgery and led to acceptably low rates of failure and complication [ 29 ]. However, a global study on the effect of COVID-19 on pediatric surgery, in general, showed less of an effect, where only 4 out of 20 institutes were found to begin using NOT for appendicitis, and 14 out of 20 reported that they had not changed their extent of NOT use [ 30 ].…”
Section: Discussionmentioning
confidence: 99%